Aluminum-based drinking-water treatment residuals: a novel sorbent for perchlorate removal - Sarkar, Dibyendu; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2006)
Perchlorate contamination of aquifers and drinking-water supplies has led to stringent regulations in several states to reduce perchlorate concentrations in water at acceptable levels for human consumption. Several perchlorate treatment technologies exist, but there is significant cost associated with their use, and the majority of them are unable to degrade perchlorate to innocuous chloride. We propose the use of a novel sorbent for perchlorate, i.e. an aluminum-based drinking-water treatment residual (Al-WTR), which is a by-product of the drinking-water treatment process. Perchlorate sorption isotherms (23 ± 1 °C) showed that the greatest amount (65%) of perchlorate removed by the Al-WTR was observed with the lowest initial perchlorate load (10 mg L−1) after only 2 h of contact time. Increasing the contact time to 24 h, perchlorate removal increased from 65 to 76%. A significant correlation was observed between the amounts of perchlorate removed with evolved chloride in solution, suggesting degradation of perchlorate to chloride.
Keywords: Perchlorate; Chloride; Drinking-water treatment residuals; Adsorption; Desorption